Possessive Pronoun Alternation as a Morphological Feature of the Gane Language in South Halmahera Regency - Nurain Jalaluddin; Rahma Do Subuh; Bakhtiar Majid (CV. Eureka Murakabi Abadi, 2026)
This study investigates the distinctive morphological characteristics of the Gane language spoken in Foya village, East Gane sub-district, South Halmahera Regency. A defining feature of Gane is the systematic alternation of possessive pronoun forms conditioned by the semantic class of the possessed noun. The analysis focuses on two primary possessive pronoun forms that reflect a semantic classification system based on nominal categories. This study aims to describe the morphological forms of Gane possessive pronouns and document their usage patterns within the grammatical and cultural context of the speech community. Data was collected through the observation and elicitation methods, employing direct elicitation; interviews, and direct transcription of Gane speech. Data analysis employed structural morphological analysis and distributional analysis to trace the distinctions between the two possessive pronoun forms. The findings reveal that the first form of possessive pronouns (e.g.,anik/nik, amam, iterir, anim/nim, ini/ni, siriri) is used to express ownership of general objects such as houses or boats, while the second form (e.g., anak/nak, inam/nam, ino/no, sirori) is employed to indicate possession of food-related items. The morphological alternation phenomena (vowel shortening and morpheme substitution) indicate processes of phonological regularization and semantic categorization within the Gane possessive pronoun system. These findings demonstrate that Gane preserves morphological features characteristic of the Eastern Austronesian language family. These distinctive morphological traits not only provide evidence that the language spoken in Foya village is Gane rather than a separate “Foya language” as claimed by some local speakers but also constitute valuable data for future research into related languages across the region, potentially illuminating historical migration patterns and language dispersal.